Auto-Play Media Studio 8 based on Blended Learning: An Effort to Optimization of Teacher Competency - Fitria Lestari; Noprisa Noprisa; Dwi Desmayanasari; Desrina Hardianti; Deni Efendi; Andika Eko Prasetiyo (FOUNDAE (Foundation of Advanced Education), 2021)
Advances in science and technology have brought enormous changes to the advancement of education, especially for teachers to improve pedagogical competence. Therefore, teachers must be able to design learning that can transfer knowledge and information well to students. This service program was carried out at SMP N 7 Pesawaran with the aim of providing assistance to teachers in the interactive learning of Auto Play Media Studio 8 (AMS) based on blended learning. The methods used in this training include training on AMS 8 applications that produce products made by participants using the ADDIE development. The results of this service (1) increase teacher knowledge and skills by 92,9% of the 44 participants, 85,3% of teachers on average are able to implement blended learning-based Auto Play Media Studio 8 (AMS) learning media (2) help answer learning at this time, especially in the Covid-19 pandemic conditions which causes students to not be able to learn directly by coming to school so that teachers can apply innovative learning to increase student motivation in learning.